2003
DOI: 10.1159/000070811
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Analysis of Fetal Heart Rate Variability in Fetuses with Supraventricular Extrasystoles

Abstract: Objective: Fetal heart rate (FHR) variability is an important indicator of fetal well-being. In fetal tachyarrhythmias, however, visual analysis of FHR variability is limited. We therefore applied power spectral analysis of FHR to evaluate the fetal state. Methods: Fetal R-R intervals were detected by means of an external ECG in 3 fetuses with supraventricular extrasystoles after cardiac malformations had been excluded by fetal echocardiography. Using an autoregressive model, power spectral densities were calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…27 were in contrast with the values and trends already available. 34 Although in fetal studies the significance of such parameters is still highly speculative, the outcome of the present study might suggest a possible unbalance between sympathetic and parasympathetic innervations, as already indicated in another study 30 ; this transitory unbalance might play a pathogenetic role in the occurrence of fetal arrhythmias.…”
Section: Analysis Of Heart Rate Variability (Hrv)supporting
confidence: 66%
See 2 more Smart Citations
“…27 were in contrast with the values and trends already available. 34 Although in fetal studies the significance of such parameters is still highly speculative, the outcome of the present study might suggest a possible unbalance between sympathetic and parasympathetic innervations, as already indicated in another study 30 ; this transitory unbalance might play a pathogenetic role in the occurrence of fetal arrhythmias.…”
Section: Analysis Of Heart Rate Variability (Hrv)supporting
confidence: 66%
“…Spectral analysis of fetal heart rate variability may help in the classification of arrhythmias and in the assessment of the functional state of the fetal autonomous nervous system (ANS): 30–32 a variability >5 beats/min is generally considered an indicator of fetal well‐being.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This requires a deeper understanding of the physiological meaning of fHRV complexity, including how its linear and nonlinear properties are modulated by sympathetic and vagal activity of the autonomic nervous system (ANS). Understanding fHRV dynamics during physiological (e.g., sleep states dependent changes) and pathophysiological (e.g., asphyxia) conditions has evolved over the past two decades, propelled by analyses of the linear aspects of fHRV in human and ovine fetuses (4,11,16,20,29,32). However, characterization of the linear fHRV properties is fundamentally limited in its power to describe the nonlinear structure of the underlying sympathovagal interactions (12,14).…”
mentioning
confidence: 99%
“…Experimental and clinical studies have shown arrhythmia in fetuses (Clancy et al, 2007;Srinivasan and Strasburger, 2008;Zhao et al, 2008). Most of previous studies on fetal arrhythmia were related to abnormal development (Zhao et al, 2008;Hahurij et al, 2008;Troeger et al, 2003), only a few studies determined environmental eff ects on fetal arrhythmia (Quigley et al, 1979;Habek, 2007). Patterns of fetal arrhythmia found in utero in previous studies were either tachycardia or bradycardia (Quigley et al, 1979;Clancy et al, 2007).…”
Section: Discussionmentioning
confidence: 99%